Skeletal Muscle Mitochondrial Adaptations to Maximal Strength Training in Older Adults - Berg, Ole Kristian; Kwon, Oh Sung; Hureau, Thomas J; Clifton, Heather L; Thurston, Taylor S; Le Fur, Yann; Jeong, Eun-Kee; Trinity, Joel D; Richardson, Russell S; Wang, Eivind; Layec, Gwenael (The journals of gerontology. Series A, Biological sciences and medical sciences, 2020)
Maximal strength training (MST) results in robust improvements in skeletal muscle force production, efficiency, and mass. However, the effects of MST on muscle mitochondria are still unknown. Accordingly, the purpose of this study was to examine, from the molecular level to whole-muscle, mitochondrial adaptations induced by 8 weeks of knee-extension MST in the quadriceps of 10 older adults using immunoblotting, spectrophotometry, high-resolution respirometry in permeabilized muscle fibers, in vivo 31P magnetic resonance spectroscopy (31P-MRS), and gas exchange. As anticipated, MST resulted in an increased isometric knee-extensor force from 133 ± 36 to 147 ± 49 Nm (p < .05) and quadriceps muscle volume from 1,410 ± 103 to 1,555 ± 455 cm3 (p < .05). Mitochondrial complex (I-V) protein abundance and citrate synthase activity were not significantly altered by MST. Assessed ex vivo, maximal ADP-stimulated respiration (state 3CI+CII, PRE: 23 ± 6 and POST: 14 ± 5 ρM·mg-1·s-1, p < .05), was decreased by MST, predominantly, as a result of a decline in complex I-linked respiration (p < .05). Additionally, state 3 free-fatty acid linked respiration was decreased following MST (PRE: 19 ± 5 and POST: 14 ± 3 ρM·mg-1·s-1, p < .05). Assessed in vivo, MST slowed the PCr recovery time constant (PRE: 49 ± 13 and POST: 57 ± 16 seconds, p < .05) and lowered, by ~20% (p = .055), the quadriceps peak rate of oxidative ATP synthesis, but did not significantly alter the oxidation of lipid. Although these, likely qualitative, mitochondrial adaptations are potentially negative in terms of skeletal muscle energetic capacity, they need to be considered in light of the many improvements in muscle function that MST affords older adults.